Occupational Exposure to Airborne Bacteria During Handling Refuse-Derived Fuel from Municipal Solid Waste Used for Clinker Burning - Marcin Cyprowski; Agata Stobnicka-Kupiec; Anna Ławniczek-Wałczyk; Małgorzata Gołofit-Szymczak; Rafał L. Górny (Aerosol and Air Quality Research)
Abstract Introduction Cement plants use refuse-derived fuel (RDF) as an important energy source in cement production. Objective The aim of the study was to characterize bacterial contamination of RDF and air at workplaces related to their combustion process. Methods The study was carried out in 4 cement plants in Poland. Bioaerosol sampling covered different stages of technological process of fuel combustion. Fourteen RDF samples were also collected. Quantitative and qualitative analysis of bacteria was performed using API biochemical tests. Results The median bacterial concentration found in RDF samples was at the level of 4.2 × 106 CFU g−1 (1.1 × 105–2.9 × 1012 CFU g−1). Median concentration values of airborne bacteria amounted to 1.9 × 104 CFU m−3 (1.9 × 102–1.1 × 105 CFU m−3). Concentrations exceeded the threshold limit values for bacteria in the loader cabin (1.1 × 105 CFU m−3, 1.1 × 105–1.2 × 105 CFU m−3) and laboratory rooms (1.3 × 104 CFU m−3, 1.9 × 102–1.1 × 105 CFU m−3). Bioaerosol concentrations significantly correlated with air temperature and relative humidity (p < 0.001). Gram-positive bacilli, as well as Gram-negative rods i.e. Enterobacter, Escherichia, Klebsiella, and Proteus genera were widely present in bioaerosol samples. This study confirmed, the ubiquity of 21 bacterial species classified in risk group 2 according to Directive 2019/1833 in both bioaerosol and alternative fuel samples. Conclusion In conclusion, RDF significantly affect the air quality at workplaces in cement plants. Therefore, employers should consider implementing various technical, organizational, and personal measures to protect exposed workers. Graphical Abstract